2023
DOI: 10.3390/nu15143130
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Circulating Lipids and Female Infertility Risk: A Univariable and Multivariable Mendelian Randomization Analysis

Abstract: Background: Although observational studies have demonstrated that blood lipids are associated with female infertility, the causality of this association remains unclear. We performed a univariable and multivariable Mendelian randomization (MR) analysis to evaluate the causal relationship between blood lipids and female infertility. Methods: Single-nucleotide polymorphisms associated with lipid traits in univariate analysis were obtained from the Million Veteran Program (MVP) and Global Lipids Genetics Consorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“… 97 Nevertheless, higher lipid storage in the form of lipid droplets can progressively lead to chronic tissue injury via these cellular stress responses and eventually fibrosis or cancer, such as that reported in fatty liver. 119 , 120 Although associations between systemic dyslipidemia and infertility have been reported, 8 12 , 121 , 122 the potential clinical consequences of higher lipid droplet accumulation in ovarian cells remain virtually unexplored.…”
Section: Discussionmentioning
confidence: 99%
“… 97 Nevertheless, higher lipid storage in the form of lipid droplets can progressively lead to chronic tissue injury via these cellular stress responses and eventually fibrosis or cancer, such as that reported in fatty liver. 119 , 120 Although associations between systemic dyslipidemia and infertility have been reported, 8 12 , 121 , 122 the potential clinical consequences of higher lipid droplet accumulation in ovarian cells remain virtually unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TG, HDL-C and hs-CRP were identified as independent risk factors for unexplained infertility [ 43 ]. In contrast, an MR study revealed that the likelihood of female infertility was raised by 13% and 16% for every incremental rise in LDL-C and TC levels, respectively, and there was no evidence that HDL-C was prominently related to female infertility risk [ 44 ]. Notably, HDL is the primary lipoprotein present in ovarian follicular fluid (FF), which is mainly derived from plasma [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A causal relationship between exposure factors and outcome was indicated only when the p -value of the IVW method was less than 0.05. When assuming that all SNPs are valid IVs, the IVW method can provide a valid estimate of the causal relationship between exposure factors and outcome ( Zhu et al, 2023 ). In addition, the results of MR analysis were visualized through scatter plots, forest plots and funnel plots.…”
Section: Methodsmentioning
confidence: 99%